Treatment of alcoholic liver disease - Thomas H. Frazier MD; Abigail M. Stocker MD; Nicole A. Kershner MD; Luis S. Marsano MD; Craig J. McClain MD (Therapeutic Advances in Gastroenterology, 2011)
Alcoholic liver disease (ALD) remains a major cause of liver-related mortality in the US and worldwide. The correct diagnosis of ALD can usually be made on a clinical basis in conjunction with blood tests, and a liver biopsy is not usually required. Abstinence is the hallmark of therapy for ALD, and nutritional therapy is the first line of therapeutic intervention. The role of steroids in patients with moderate to severe alcoholic hepatitis is gaining increasing acceptance, with the caveat that patients be evaluated for the effectiveness of therapy at 1 week. Pentoxifylline appears to be especially effective in ALD patients with renal dysfunction/hepatorenal syndrome. Biologics such as specific anti-TNFs have been disappointing and should probably not be used outside of the clinical trial setting. Transplantation is effective in patients with end-stage ALD who have stopped drinking (usually for ≥6 months), and both long-term graft and patient survival are excellent.